The Influence Of The Implementation Of Experiential Learning On Mathematics Learning Outcomes At SD Inpres Layang Tua II In Makassar - Khaerun Nisa'a Tayibu; Rahmah Kumullah (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2021)
This study aims to (1) know the description of the implementation of the experiential learning model in class V SD Inpres Layang Tua II Makassar City, (2) to know the description of the Mathematics learning outcomes of students of SD Inpres Layang Tua II Makassar City, (3) to determine the effect of implementing the experiential model. learning about Mathematics learning outcomes in students of SD Inpres Layang Tua II Makassar City. This type of research is a true experimental research design involving one experimental class and one control class. The research location is in SD Inpres Layang Tua II, Makassar City. The design of this study was a pretest-posttest control group design. The population of this research is the fifth grade students of SD Inpres Layang Tua II Makassar City with a sample of 20 control classes and 20 experimental classes taken randomly. The independent variable in this study is the implementation of the experiential learning model and the dependent variable is the Mathematics learning outcome. Data collection techniques in this study were tests, observation and documentation. The research instrument was a Mathematics learning outcome test with 23 items and a lesson plan (RPP). The data obtained were analyzed by two types of statistics, namely descriptive statistical tests and inferential statistics including: Data Normality Test, Data Homogeneity Test and Hypothesis Test. The results showed that: (i) the application of the experiential learning model in Mathematics learning for fifth grade students of SD Inpres Layang Tua, Makassar City, which consists of concrete experience stages, observation reflection, abstract concepts and applications generally go well, (ii) Mathematics learning outcomes The fifth grade students of SD Inpres Layang Tua II in Makassar City in the pre-test experimental class were lower than the control class with an average score of 47 for the experimental class and 52 for the control class. Meanwhile, in the post-test the experimental class was higher than the control class with an average score. -The experimental class average is 79 and the control class is 70, (iii) there is an effect of the application of the experiential learning model on the Mathematics learning outcomes of class V SD Inpres Layang Tua II Makassar City after hypothesis testing is 0.004 <0.05.